The Impact of Blockchain Technology on Administrative Processes: Enhancing Transparency, Efficiency, and Trust - Farikhul Muafiq (Education Studies and Teaching Journal (EDUTECH), 2024)
Blockchain technology has attracted significant attention due to its potential to revolutionize administrative processes by increasing transparency, efficiency and trust. This systematic literature review (SLR) aims to provide insight into the impact of blockchain technology on administrative processes, as well as the challenges and risks associated with its implementation. Through a comprehensive literature review, this study explores the main challenges faced by organizations in adopting blockchain technology in their administrative processes and investigates strategies and solutions to reduce security, privacy, and governance risks. Additionally, practical recommendations are offered for organizations considering or currently undergoing blockchain implementation in their administrative processes. The findings highlight the transformative potential of blockchain technology in improving administrative processes across a wide range of sectors, while also emphasizing the need to address technical, security, governance and regulatory challenges. Additionally, a framework and guidelines for effective blockchain implementation are proposed, with a focus on secure design principles, best practices in maintaining data security and privacy, and the establishment of a governance model and regulatory framework. However, it is acknowledged that this study has limitations, including the scope of the available literature and the possibility of new developments in blockchain technology that have not been uncovered in this review. Future research is needed to address these limitations and further explore the implications of blockchain implementation in an administrative context. Overall, this study provides valuable insights to our understanding of the potential and challenges associated with the use of blockchain technology in improving efficiency and transparency in administrative processes